Electronic Structure of Molecular Magnets - Schmidt, Norman Anja; Graf-Zeiler, Birgit; Scheurer, Andreas; Prakash, Raju; Saalfrank, Rolf; Goering, E.; Fink, Rainer (BESSY Annual Reports 2006, 2006)

In situ synchrotron radiation X-ray microspectroscopy of polymer microcontainers - Graf-Zeiler, Birgit; Fink, Rainer; Tzvetkov, George (ChemPhysChem, 2011)
Direct, real-time analytical techniques that provide high-resolution information on the chemical composition and submicrometer structure of various polymer micro- and nanoparticles are in high demand in a range of life science disciplines. Synchrotron-based scanning transmission X-ray microspectroscopy (STXM) combines both local-spot chemical information (assessed via near-edge X-ray absorption fine structure spectroscopy) and imaging with resolution of several tens of nanometers, and thus can yield new insights into the nanoscale properties of these materials. Furthermore, this method allows in situ examination of soft-matter samples in aqueous/gaseous environments and under external stimuli, such as temperature, pressure, ultrasound, and light irradiation. This Minireview highlights some recent progress in the application of the STXM technique to study the temperature-dependent behavior of polymer core-shell microcapsules and to characterize the physicochemical properties of the supporting shells of gas-filled microbubbles in their natural hydrated state. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Quantitative X-ray microscopic analysis of individual thermoresponsive microgel particles in aqueous solution - Späth, Andreas; Graf-Zeiler, Birgit; Paradossi, Gaio; Ghugare, Shivkumar V.; Tzvetkov, George; Fink, Rainer H. (RSC Advances, 2016)

Water-dispersible PVA-based dry microballoons with potential for biomedical applications - Tzvetkov, George; Paradossi, Gaio; Tortora, Mariarosaria; Fernandes, Paulo; Fery, Andreas; Graf-Zeiler, Birgit; Fink, Rainer (Materials Science and Engineering C, 2010)
This paper reports on the preparation and characterization of stable poly(vinyl alcohol) (PVA)-based dry hollow microparticles, readily convertible to gas-filled microballoons (MBs) in water suspension. The rehydrated MBs can be used as ultrasound contrast agents and for targeted drug delivery, while the dry MBs are suitable for encapsulation of biologically active gases. The MBs powder material is obtained by freeze-drying the as-prepared telechelic PVA-shelled MBs aqueous dispersion. The microstructure of the lyophilized MBs as well as of the starting and the reconstituted MBs in water suspension was examined using transmission electron microscopy (TEM), scanning electron microscopy (SEM), scanning transmission X-ray microspectroscopy (STXM) and confocal laser scanning microscopy (CLSM). STXM observations below and above the oxygen K-edge reveal that 80% of the MBs originating from the lyophilized particles are gas-filled. Moreover, local carbon K near-edge X-ray absorption fine structure spectroscopy (NEXAFS) measurements evidenced that the chemical composition of the polymeric shell is preserved during the freeze-drying process and subsequent shelf storage for at least more than one year. © 2010 Elsevier B.V. All rights reserved.